2020
DOI: 10.1136/bmjopen-2019-036557
|View full text |Cite
|
Sign up to set email alerts
|

Association between family functions and antenatal depression symptoms: a cross-sectional study among pregnant women in urban communities of Hengyang city, China

Abstract: ObjectiveTo explore the prevalence of depressive symptoms among women in late pregnancy, and assess mediating effect of self-efficacy in the association between family functions and the antenatal depressive symptoms.DesignCommunity-based, cross-sectional study was conducted among women during the third trimester of pregnancy.SettingThis study was conducted among pregnant women registered at community health service centres of urban Hengyang City, China from July to October 2019.Participants813 people were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…A análise dos dados apontou que 46 mulheres (69,7%, IC95% 57,6-81,8) viviam com algum companheiro, o que pode relacionar-se com o aumento dos escores das respostas das questões para o instrumento APGAR de Família, que impactou em uma maior prevalência, isto é 76,6% (IC95% 65,6-87,5), de famílias com boa funcionalidade entre as gestantes analisadas. Estudos demonstraram que o apoio familiar e do companheiro influenciam de forma assertiva o período gestacional (CALDEIRA et al, 2017;ZHENG et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A análise dos dados apontou que 46 mulheres (69,7%, IC95% 57,6-81,8) viviam com algum companheiro, o que pode relacionar-se com o aumento dos escores das respostas das questões para o instrumento APGAR de Família, que impactou em uma maior prevalência, isto é 76,6% (IC95% 65,6-87,5), de famílias com boa funcionalidade entre as gestantes analisadas. Estudos demonstraram que o apoio familiar e do companheiro influenciam de forma assertiva o período gestacional (CALDEIRA et al, 2017;ZHENG et al, 2020).…”
Section: Resultsunclassified
“…Na análise da funcionalidade familiar pela amostra estudada, encontrou-se similaridade com outros estudos internacionais no que tange ao instrumento utilizado e a população escolhida (NAKAMURA; SATO; WATANABE, 2018;TSAI, 2019;ZHENG et al, 2020). Contudo, até o momento de finalização do relatório de IC, não se encontrou estudos que versaram sobre os domínios do APGAR de Família nas relações familiares de gestantes, denotando que a presente pesquisa se revelou inédita quando se propôs a analisá-los.…”
Section: Resultsunclassified
“…Although the above‐mentioned evidence indicates that women with depression tend to have poor maternal role competence, maternal self‐efficacy potentially buffers this relationship 13 . Maternal self‐efficacy is defined as a mother's belief in her abilities to organize and execute tasks dealing with parenting children 14 . Regardless of actual skill or ability (competence), maternal self‐efficacy alone is a vital index for a successful transition to motherhood and positive maternal behavior 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Family function is more crucial for pregnant women in the families from Asia and other countries with a Confucian cultural context [ 30 , 31 ]. A cross-sectional study in China found that the risk of depression symptoms in pregnant women who had poor family function was 3.67 times as much as that in the better functions group [ 32 ].…”
Section: Introductionmentioning
confidence: 99%